Interconnection of Peremptory Norms of International Law and erga omnes Obligations - S. V. Chernichenko (Московский журнал международного права, 2012)
The content of peremptory norms is always erga omnes obligations. The mirror conclusion is also correct: erga omnes obligations always mean the content of peremptory norms.It is impossible to give a list of peremptory norms and the content of erga omnes obligations. The principles of international law can be regarded as peremptory norms. It does not rule out the interpretation of them. Some provisions of the Declaration of principles of International law (1970) can also be regarded as concretizing peremptory norms.The concluding of an international treaty creating more favorable conditions for its participants which does not contradict peremptory norms should not be related to the violation of peremptory norms.The hierarchy of peremptory norms should not be understood as the priority of some norms in comparison with other ones. The development of inter-State relations and the development of international law make possible collisions between peremptory norms.It is possible to suppose the existence of regional peremptory norms or a linking group of States by another indication, on the condition that they do not contradict global peremptory norms.The Commission of International Law took a decision not to use the term “international crimes” preferring the term having a broader meaning “serious breach of a peremptory norm”.